Addressing mental health need after COVID-19: a systematic review of remote EMDR therapy studies as an emerging option - Kaptan, Safa Kemal; Kaya, Zehra Merve; Akan, Ayşe (Frontiers in Psychiatry, 2024)
Introduction: The COVID-19 pandemic has been associated with a substantial rise in mental health challenges, prompting a need for accessible and effective therapeutic interventions. This review summarizes the evidence on remote Eye Movement Desensitization and Reprocessing (EMDR) therapy delivered in response to the increased need. Methods: A systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Databases including PsychINFO, EMBASE, MEDLINE, and Web of Science were searched to identify studies assessing the efficacy of EMDR therapy administered online. Results: Sixteen articles meeting the inclusion criteria were selected, involving 1231 participants across various age groups. Studies covered remote individual and group EMDR sessions and self-administered computerized protocols. Findings indicate promising outcomes in reducing PTSD symptoms, anxiety, and depression.Discussion: The analysis of the selected studies demonstrates the feasibility and potential efficacy of online EMDR as an accessible therapeutic option for addressing mental health difficulties, particularly during times of limited in-person interaction. However, the studies revealed limitations such as small sample sizes, absence of control groups, and reliance on selfreported measures.